2022
DOI: 10.1177/10901981221084266
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Duration of School Garden Exposure and Self-Reported Learning and School Connectedness

Abstract: When students feel connected to their school, they experience positive health and academic outcomes. In contrast, school disengagement is a predictor of dropout, delinquency, and substance use. School garden programming has the potential to help children achieve academic outcomes and feel connected to their school. Unfortunately, most school garden research has been conducted with white, affluent study participants. We describe the results of a secondary analysis utilizing data from an evaluation of a universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The school garden is the right place for active learning for various subjects where teachers can use the school garden as a laboratory for conducting experiments and can also be used to study mathematics, English, and art so that the teaching and learning process becomes more interesting (CSGN, 2010;Wiradnyani et al, 2018). School gardens have the potential to improve student learning outcomes (Lohr et al, 2023) Gardening activities at school can develop children's physical and motor skills, explore objects around them, and learn while playing so that children are active and don't feel bored (Sutrisno, 2005;Windarto et al, 2020). School gardens provide an active learning atmosphere that strengthens academic, personal, and social abilities (Kammar et al, 2017;Wiradnyani et al, 2018) Planting activities in school gardens in addition to increasing accessibility and availability of fruits and vegetables also encourage children to appreciate the products they produce.…”
Section: Introductionmentioning
confidence: 99%
“…The school garden is the right place for active learning for various subjects where teachers can use the school garden as a laboratory for conducting experiments and can also be used to study mathematics, English, and art so that the teaching and learning process becomes more interesting (CSGN, 2010;Wiradnyani et al, 2018). School gardens have the potential to improve student learning outcomes (Lohr et al, 2023) Gardening activities at school can develop children's physical and motor skills, explore objects around them, and learn while playing so that children are active and don't feel bored (Sutrisno, 2005;Windarto et al, 2020). School gardens provide an active learning atmosphere that strengthens academic, personal, and social abilities (Kammar et al, 2017;Wiradnyani et al, 2018) Planting activities in school gardens in addition to increasing accessibility and availability of fruits and vegetables also encourage children to appreciate the products they produce.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the design and creation of a school garden improves students' academic performance and through the active participation of students, positive attitudes towards school and their interest in learning are developed (Austin, 2022;Blair, 2009;Broda, 2007;Deniz et al, 2022;Korfiatis & Petrou, 2015;Pollin & Retzlaff -Fürst, 2021). More specifically, research can be identified at the international level that deals with the measurement of students' learning performance during their experiential engagement in the school garden (Garitsis, 2016;Lohr et al, 2022). In particular, an extensive study (Graham & Zidenger -Cherr, 2005, cited in Garitsis, 2016) investigated teachers' perceptions regarding the impact of school gardens on student teaching and learning in all schools in the state of California in the context of a project implementation entitled: "A garden in every school".…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show that cooperation in the context of students' work groups during their engagement with the school garden has benefits in other areas of school life, such as communication and problem-solving skills, attitudes towards school, social and emotional learning, acceptance of diversity (Garitsis, 2016;Lohr et al, 2021;Lohr et al, 2022;Strom & Strom, 1996;Waliczek et al, 2001). Typically, regarding the acceptance of diversity, the school garden provides an opportunity to engage immigrant parents or parents who have agricultural rather than academic knowledge (Greer et al, 2019;Lohr et al, 2022;Ozer, 2006;Sotiropoulou, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations